Transposition of basilic vein for vascular access for haemodialysis: an experience of a tertiary care hospital - Hussain, Tahir; Farooqui, Fareeha; Bin Pervez, Muhammad; Aimen, Sibgha (Journal of the Pakistan Medical Association, 2022)
Basilic vein transposition (BVT) is the preferred permanent haemodialysis access due to better patency and lower infection rates compared to synthetic grafts. The outcomes of BVT cases, performed at Shifa International Hospital, Islamabad, from March 2006 to June 2018, were ambispectively investigated. The primary patency of the fistula was assessed immediately after surgery, at 24 hours, at 7-14 days, at 6-8 weeks and then at 3-6 months. A total of 160 patients were included in the study, out of which 83 (51.87%) were males while 77 (48.12%) were females. Of the total 160 patients, 119 (74.4%) underwent one stage BVT, while 41 (25.6%) underwent two stage BVT. One hundred and thirty-five (84.4%) procedures were successful and survived while in 25 (15.6%) cases it failed. Mean basilic vein diameter was 2.712 (±0.772) mm. Overall, 10(6.3%) patients had bleeding, 15(9.4%) fistulae thrombosed, 6(3.8%) had steal syndrome and only 1 (0.6%) patient developed pseudo aneurysm. We conclude that BVT is a feasible technique with very good patency rate especially for those patients who have multiple forearm AVF surgeries. Key words: Arteriovenous Fistula (AVF), Basilica Vein Transposition (BVT), Permanent Vascular Access, End Stage Renal Disease (ESRD).